Era uma vez... João e o Pé de Feijão - Emerick, Márcia Aparecida de Oliveira; Castro, Alcione; Ximenes, Elmira Lino; Bordinhão, Andréa Chiozini; Carraro, Márcia Regina Simpione (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
VER PDF